Fatores associados à condição de saúde bucal de pacientes internados em hospitais públicos do município de Natal-RN - Lima, Lailson Silva de (2007)
The hospitalization is an event that can attack any person, independent of gender, race, social and economical condition. Last year, the prevalence of hospitalization was 8.1 for 100 inhabitants and the average time of hospitalization was 8.5 days for each patient one in Natal city. Therefore, an important point is whether the attention to the patients during the permanence in these health establishments incorporates the health integral model suggested by the principles proposed by the National Health System in Brazil (SUS), with actions of promotion and protection by different kinds of professionals, beside those called convalescence. Then, the aim of this study was to evaluate the patient s oral health conditions hosted in public hospitals of the Natal city, looking for to establish its relationship with several risk factors by two dimensions: the characteristics of the hospitalization and the patient s general and economical conditions. We accomplished a cross-sectional study with 205 patients distributed among the hospitals Onofre Lopes, Giselda Trigueiro and Monsenhor Walfredo Gurgel, looking for to know the socio-demographic characteristics, the food habits and of oral hygiene and the conditions of oral health, through the Visible Plaque Index and Gingival Bleeding Index. We observed that the conditions of the patient s oral health interned at public hospitals of reference of the municipal district of Natal is bad, existing accumulation of dental plaque and, consequently, a great number of patients with gingival bleeding. However, the time of hospitalization and its reason, the type of medicine used in this time and the toothbrush frequency were not configured as risk factors for this oral health condition